2021
DOI: 10.3389/fendo.2021.665874
|View full text |Cite
|
Sign up to set email alerts
|

A Testis-Specific Long Noncoding RNA, Start, Is a Regulator of Steroidogenesis in Mouse Leydig Cells

Abstract: The testis expresses many long noncoding RNAs (lncRNAs), but their functions and overview of lncRNA variety are not well understood. The mouse Prss/Tessp locus contains six serine protease genes and two lncRNAs that have been suggested to play important roles in spermatogenesis. Here, we found a novel testis-specific lncRNA, Start (Steroidogenesis activating lncRNA in testis), in this locus. Start is 1822 nucleotides in length and was found to be localized mostly in the cytosol of germ cells and Leydig cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 107 publications
(133 reference statements)
0
14
0
Order By: Relevance
“…Start , an lncRNA at this locus, is expressed in both Leydig cells and germ cells. In our previous study, we verified that Start regulates the production of testosterone via activation of two steroidogenic genes, Star and Hsd3b1 , in Leydig cells [ 30 ]. Localization of Start in the cytosol of Leydig cells led to the presumption that the steroidogenic genes are regulated at the posttranscriptional level by Start .…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Start , an lncRNA at this locus, is expressed in both Leydig cells and germ cells. In our previous study, we verified that Start regulates the production of testosterone via activation of two steroidogenic genes, Star and Hsd3b1 , in Leydig cells [ 30 ]. Localization of Start in the cytosol of Leydig cells led to the presumption that the steroidogenic genes are regulated at the posttranscriptional level by Start .…”
Section: Introductionmentioning
confidence: 84%
“…The experimental procedures used in this study were approved by the Institutional Animal Use and Care Committee at Hokkaido University. Start -KO mice were generated as previously described [ 30 ]. The mice were maintained on 14 hr light/10 hr dark cycles at 25℃ and given food and water ad libitum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Start (steroidogenesis activating lncRNA in testis) is a lncRNA with a regulatory role in the testis. It is Leydig specific and may regulate steroidogenesis [Otsuka et al, 2021]. CRISPR/Cas9-generated Start knockout (KO) mice showed an increased expression of genes involved in steroidogenesis, such as Star and Hsd3b1, as demonstrated by RNA-seq and RT-qPCR.…”
Section: Steroidogenesismentioning
confidence: 99%
“…Indeed, lncRNAs were proved to take part in spermatogenesis by deleting hundreds of testicular-specific lncRNAs in the non-mammal drosophila [ 8 ]. Kai Otsuka et al found that lncRNA Start transcripted at Prss/Tessp sites acted on Leydig cells to fine-tune steroid production pathways subtly in the testis in mice [ 9 ]. Another testicular germ cell-specific lncRNA, Teshl, preferentially regulated gene expression of the Y chromosome and maintained progeny sex ratio [ 10 ].…”
Section: Introductionmentioning
confidence: 99%